2006
DOI: 10.1007/s00384-006-0089-6
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous colorectal adenocarcinoma and gastrointestinal stromal tumor (GIST)

Abstract: Synchronous CRC and GIST has been more frequently reported. Because of the limited number of cases, we cannot exclude an incidental relationship. The genetic pathways of tumorigenesis appear different for the two neoplasms. Further studies are needed to clarify a possible role of c-Kit in the development of colonic adenocarcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
34
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 27 publications
1
34
0
Order By: Relevance
“…A review of case reports in the literature showed that stromal tumours of the small intestine are mostly small and are associated with low to intermediate risk when classified according to Fletcher's risk classification [17]. (Tables 1 and 2) [4,10,12,13,[18][19][20][21][22][23]. The presented case also had a small ileum-originated low-risk GIST.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review of case reports in the literature showed that stromal tumours of the small intestine are mostly small and are associated with low to intermediate risk when classified according to Fletcher's risk classification [17]. (Tables 1 and 2) [4,10,12,13,[18][19][20][21][22][23]. The presented case also had a small ileum-originated low-risk GIST.…”
Section: Discussionmentioning
confidence: 99%
“…Why GISTs are seen with other malignant tumours is not well understood. The hypothesis, based on a few experimental studies, is that a single carcinogen or carcinogenic pathway plays a role in the neoplastic proliferation of cell series from different histological subtypes [4]. Taking this into account, it can be suggested that cell stimulation is achieved via the same carcinogenic factor during the proliferation of both epithelial and stromal cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, gene mutations predisposing to the development of various types of neoplasms may play a role. Melis et al (6) failed to find evidence of common mechanisms in the pathogenesis of GISTs and colorectal adenocarcinoma. In their case report, Kaffes et al (7) indicated that Helicobacter pylori (H. pylori) infection was a favoring factor.…”
mentioning
confidence: 99%